Anāgatavaṃsa desanā = The sermon of the chronicle-to-be - Măddēgama, Udaya Praśānta (Buddhist traditions, 1993)
Free prose transaltion of Anāgatavaṃsa desanā, an adaptation of the Anāgatavaṃsa by Kassapathēra, fl. 1160-1230, on the story of Maitreya, Buddhist deity.